The Correlation of Perceived Parenting Styles on Miriam College Nuvali High School Students’ Introversion-Extraversion Traits - Dizon, Rohann Gabriel D. (Animo Repository, 2023)
This study aims to assess the correlation strength between parenting styles and introversion/extraversion (IE) in youngsters. Previous studies popularized the predictive role of parenting in children's social skills and development, but less data is shown on its correlation with personality traits. The research collected 113 survey responses from 397 Miriam College Nuvali high school students. The researchers utilized Pearson’s correlation to determine the correlation coefficient and analysis of variance for data significance. The correlation coefficient for each parenting style with both introversion-extraversion traits averaged 0.085, with all coefficients being less than 0.2. This dictates a relatively low correlation between parenting styles and introversion-extraversion. The p-value for all computations showed 0 or near 0, which depicts significant data where the conclusion applies to the rest of the population. The low correlation coefficient is likely due to mediating variables not present in the study, such as innate introversion-extraversion traits or environmental differences.